Agent and Customer Experiences of Digital Service Innovation in Sharia Insurance: A Qualitative Study of Digital Service Platforms at a Sharia Insurance Branch in Medan - Fidya Purnama; Nuri Aslami; Nur Ahmadi Bi Rahmani (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2025)
The rapid digitalisation of Indonesia’s sharia insurance industry has not been matched by an equally rich understanding of how agents and customers experience it daily, particularly whether efficiency gains are matched by faithful communication of sharia values. This study examines the role of information technology and innovation in digital sharia insurance services at PT Prudential Syariah, Medan Branch. A descriptive-analytic qualitative approach was used, with four informants two active agents and two customers of at least one year selected through purposive sampling for their sustained engagement with the PRUServices application and the E-Withdrawal feature. Data were collected through in-depth interviews and analysed using the interactive model of Miles, Huberman, and Saldana trustworthiness was maintained through triangulation, member checking, peer debriefing, and audit trail. The findings show that PRUServices and E-Withdrawal improved operational efficiency, transparency, and accessibility in ways informants associated with sharia openness and fairness (‘adl). However, digital-literacy gaps, uneven infrastructure, and limited understanding of concepts such as akad and tabarru’ continued to constrain adoption among older customers, and agents occupied a dual role as technical mediators and communicators of sharia values. The study concludes that successful digitalisation depends on balancing technological ease with sustained value education and personal companionship, offering practical implications for agent-training design and theoretical implications for applying diffusion-of-innovation and disruptive-innovation frameworks to value-laden financial services.